Female athletes and the menstrual cycle in team sports: Current state of play and considerations for future research - Vogel, K.; Larsen, B.; McLellan, C.; Bird, S. P. (Sports, 2024)
Over the past ten years there has been a dramatic rise in female sport participation and accompanying female professional national leagues across multiple sports, yet research has not followed suit. Although there are known variations between female and male physiology, training protocols in female sport are predominantly underpinned by research undertaken in male athletes. The hormonal variability experienced by women across the menstrual cycle, as well as the menstrual cycle variability between women, may contribute to the complexity of conducting rigorous physiological studies, leading to a paucity of robust sports-specific research that can be confidently applied to female athletes. Moreover, barriers exist in female sport that potentially limit the ability to conduct research, including the lack of full-time programs and limited resources. Recently, there has been increased interest in the potential effects of fluctuations in the female sex hormones, progesterone and oestrogen, on sport performance across different phases of the menstrual cycle. However, current research evaluating the menstrual cycle and physical performance (such as strength, speed, aerobic fitness, and athletes` perception of their performance) have shown inconsistent results. Additionally, methodological design across studies has shown little consistency, making it difficult to draw firm conclusions, which potentially prevents female athletes optimising their physical and sporting performance. It further impacts coaches and sports science researchers in their ability to provide appropriate training recommendations and educational opportunities. It is important to progress in female athlete research with an understanding of how the unique physiology of female athletes may influence their ability to physically perform in their respective sport, which requires representation in sports science research. This paper will provide an overview on current evidence and limitations within menstrual cycle research and provide considerations and directions for future research in this space within team sports.